Clinical profile of patients with adult-onset eosinophilic asthma - Jantina C. de Groot; Huib Storm; Marijke Amelink; Selma B. de Nijs; Edwin Eichhorn; Bennie H. Reitsma; Elisabeth H.D. Bel; Anneke ten Brinke (ERJ Open Research, 2016)
Adult-onset eosinophilic asthma is increasingly recognised as a severe and difficult-to-treat subtype of asthma. In clinical practice, early recognition of patients with this asthma subtype is important because it may have treatment implications. Therefore, physicians need to know the distinct characteristics of this asthma phenotype. The objective of the present study was to determine the characteristic profile of patients with adult-onset eosinophilic asthma. 130 patients with adult-onset (>18 years of age) asthma and high blood eosinophil counts (≥0.3×109 L−1) were compared with 361 adult-onset asthma patients with low (<0.3×109 L−1) blood eosinophils. Measurements included a series of clinical, functional and imaging parameters. Patients with high blood eosinophils were more often male, had less well controlled asthma and higher exacerbation rates, despite the use of higher doses of inhaled corticosteroids. They had higher levels of total IgE without more sensitisation to common inhaled allergens. In addition, these patients had worse lung function, and more often showed fixed airflow limitation, air trapping, nasal polyposis and abnormalities on sinus computed tomography scanning. Chronic rhinosinusitis, air trapping and male sex were three independent factors associated with blood eosinophilia (adjusted OR 3.8 (95% CI 1.7–8.1), 3.0 (95% CI 1.1–8.1) and 2.4 (95% CI 1.3–4.4), respectively). Patients with adult-onset asthma with elevated blood eosinophils exhibit a distinct profile, which can readily be recognised in clinical practice.